2004
DOI: 10.1161/01.cir.0000138398.77550.62
|View full text |Cite
|
Sign up to set email alerts
|

Improved Exercise Capacity and Ischemia 6 and 12 Months After Transendocardial Injection of Autologous Bone Marrow Mononuclear Cells for Ischemic Cardiomyopathy

Abstract: Background-We recently reported the safety and feasibility of autologous bone marrow mononuclear cell (ABMMNC) injection into areas of ischemic myocardium in patients with end-stage ischemic cardiomyopathy. The present study evaluated the safety and efficacy of this therapy at 6-and 12-month follow-up. Methods and Results-Twenty patients with 6-and 12-month follow-up (11 treated subjects; 9 controls) were enrolled in this prospective, nonrandomized, open-label study. Complete clinical and laboratory evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
205
0
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 283 publications
(225 citation statements)
references
References 29 publications
9
205
0
9
Order By: Relevance
“…The mechanism underlying improvement of systolic and diastolic function after bone marrow cell transplantation could be related to promotion of angiogenesis, as proposed by both preclinical and clinical studies (2,5,6,15). Patients in the current study had advanced coronary artery disease and stress-inducible myocardial ischemia, resulting in mild diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…The mechanism underlying improvement of systolic and diastolic function after bone marrow cell transplantation could be related to promotion of angiogenesis, as proposed by both preclinical and clinical studies (2,5,6,15). Patients in the current study had advanced coronary artery disease and stress-inducible myocardial ischemia, resulting in mild diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…They also showed modest but significant benefits with regard to improved left ventricular ejection fraction (LVEF), decreased infarct size, and reduced frequency of recurrent ischemic events or need for intervention. Trials of stem cell therapy for chronic postinfarction heart failure also demonstrated improvements in natriuretic peptide levels, exertional capacity, and mortality at longer than 1 year of follow-up (7,107). However, the benefit, at least in the acute setting, may be limited, as the LVEF recovery did not persist at 18 months of follow-up in the BOOST study (94).…”
Section: Ex Vivo Mesenchymal Stem Cell Modificationmentioning
confidence: 99%
“…In addition, mean ejection fraction was improved and systolic volumes were favorably reduced. 8,73 The improved perfusion may indicate that the principal effect of cell transfer was stimulation of angiogenesis leading to improved cardiac performance as a secondary effect.…”
Section: Resident Cardiac Progenitor Cellsmentioning
confidence: 99%